The Ethical Considerations of Neuromodulation: Balancing Medical Benefits with Brain Enhancement - Dr.Utpal Basu (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This research delves into the emerging field of neuromodulation, which uses electrical or magnetic stimulation to influence brain activity. It examines the potential therapeutic applications of neuromodulation for treating neurological disorders and explores the ethical considerations surrounding its use for cognitive enhancement. The research may discuss the potential risks and benefits of neuromodulation and the need for responsible advancement in this field.